Optimisation of convective heat dissipation from ventilated brake discs - Galindo-Lopez, Carlos Hannover (Cranfield University, 2009)
Fast heat dissipation from brake discs is sought in current vehicles, where high power braking duties demand harmonic combination of strength, (undamped) disc mass and cooling abilities for a wide speed range. This work analyses the convective heat dissipation from ventilated brake discs and proposes means for its optimisation. The focus of research is the ventilation geometry of a standard brake disc with an outer diameter of 434mm and radial channels of 101mm in length. After analysing in detail data calculated with CFD simulations and from experimental work for various ventilation patterns, a parameter relating the local channel-averaged convective heat transfer coefficient to channel circumferential width, and radial location was derived. This new numerical parameter termed Flow Index, depicts graphically the link between channel geometry (width and position) to the heat transfer coefficient level attained. The FI was not only used as a tool to analyse the convective performance of conventional and new ventilation geometries, but it also allowed clear identification of changes necessary in the channel width in order to improve its convective heat transfer coefficients. New, optimised for convective heat transfer, ventilation geometries designed with the FI were achieved in this Thesis. Industrial (patenting) and academic applications are foreseen from the results of this Thesis and its future activities. Also, the work developed in this Thesis gives path and supporting frame for future research in the field of brake disc convective heat dissipation.